PENGEMBANGAN DESAIN KURSI TAMAN BUNGKUL DENGAN MENGANGKAT TEMA SPARKLING SURABAYA - Suci Ramadhani (ATRIUM: Jurnal Arsitektur, 2016)
Title: Design Development of Bungkul Park Street Furniture Related to Sparkling Surabaya Theme City Park is an open green space that serves as the city's lungs and reduce the pollution and noise, and also can be a gathering place for city residents. In addition to the technical function and social function,a city park in Surabaya also raised Surabaya's image as a City which has 1001 parks. Bungkul Park is located in Darmo Street, this park is not only crowded, but also become one of an icon in Surabaya. Surabaya, which has made Sparkling Surabaya Theme became a brand since 2006, less contribute to the street furniture's design in the main streets of Surabaya and city parks. This is very unfortunate that it can be one of Surabaya's promotional event in national and international. The method of this research used comparative descriptive method, which make a systematic description, factual, and accurate about the facts and circumstances object of investigation that was followed by a comparative study to understand the interrelationships among facts. From the analysis conducted, either through observation, comparison of products, as well as literature study, the data showes that Surabaya Sparkling's elements contains typography, color and lighting factors. The final design of this research is a design of the street furniture of the park related to Sparkling Surabaya theme.